Severity of Cylindrocladium Leaf Blight in Eucalypt Plantation in Relation to Intercropping with Tapioca and Rainfall - Sharma, J. K.; Mohanan, C. (Indian Forester, 1994)
Rainfall had great influence on the severity of Cylindrocladium leaf blight, which was further intensified when an intercrop (taungya) of Manihot utilissima Pohl. was cultivated in a 2-yr-old plantation of Eucalyptus tereticornis. High severity of the disease was positively correlated with high rainfall pattern; apparently high relative humidity had little impact on disease severity.